Dosimetric characteristics of a LKB:Cu,Mg solid thermoluminescence detector - Alajerami, Yasser Saleh Mustafa; Hashim, Suhairul; Ramli, Ahmad Termizi; Mohammed Saleh, Muneer Aziz; Abdul Kadir, Ahmad Bazlie; Saripan, M. Iqbal (Chinese Physical Society, 2013)
We present the main thermoluminescence characteristics of a newly borate glass dosimeter modified with lithium and potassium carbonate (LKB) and co-doped with CuO and MgO. An enhancement of about three times has been shown with the increment of 0.1mol% MgO as a co-dopant impurity. The effects of dose linearity, storage capacity, effective atomic number and energy dose response are studied. The proposed dosimeter shows a simple glow curve, good linearity up to 103 Gy, close effective atomic number and photon energy independence. The current results suggest using the proposed dosimeter in different dosimetric applications.